Biological soil crusts from High Arctic Environments: taxonomic composition of the prokaryotic community and characterization of exopolysaccharidic matrix - MUGNAI, GIANMARCO; Ventura, S; Mascalchi, C; ROSSI, FEDERICO; ADESSI, ALESSANDRA; DE PHILIPPIS, ROBERTO (SIMGBM, 2015)
Sviluppo di croste biologiche in ambiente artico